2012
DOI: 10.1111/j.1468-1331.2012.03670.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fission proteins in peripheral blood lymphocytes are potential biomarkers for Alzheimer’s disease

Abstract: Altered mitochondrial fission proteins Drp1, SNO-Drp1, and Fis1 in PBL were relatively sensitive and specific in identifying AD patients and could be serving as a biomarker in the procedure of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…An association between dementia and mitochondrial function has also been reported. For instance, an increased number of mtDNA mutations and abnormal mitochondrial morphologic changes were found in blood [34] and brain [35] samples of Alzheimer disease patients as compared to those of control subjects. Quantitatively, our previous study showed a positive relationship between mtDNA copy number and cognitive function in non-demented elderly adults consistent with our present results [36].…”
Section: Discussionmentioning
confidence: 99%
“…An association between dementia and mitochondrial function has also been reported. For instance, an increased number of mtDNA mutations and abnormal mitochondrial morphologic changes were found in blood [34] and brain [35] samples of Alzheimer disease patients as compared to those of control subjects. Quantitatively, our previous study showed a positive relationship between mtDNA copy number and cognitive function in non-demented elderly adults consistent with our present results [36].…”
Section: Discussionmentioning
confidence: 99%
“…In support of a pathological role for S-nitrolyation of Drp1, Drp1 is apparently S-nitrosylated aberrantly because it is found at high levels in postmortem human AD brains but not in control brains [190191], as well as in peripheral blood lymphocytes of AD but not control patients [194]. …”
Section: Drp1 and Cdk5 In Alzheimer’s Diseasementioning
confidence: 99%
“…However, there is controversy over DLP1 expression: reduced DLP1 expression in AD brain was reported by Wang et al and by Bossy et al [9, 57], but not by Manczak et al who actually found increased DLP1 in AD [11]. Reduced DLP1 expression is also demonstrated in fibroblasts and lymphocytes from AD patients [10, 58]. Given that the majority of DLP1 in mammalian cells is cytosolic and mitochondrial recruitment of DLP1 represents a critical step during mitochondrial fission [18], mitochondrial DLP1 serves as a better indicator for mitochondrial fission.…”
Section: Introductionmentioning
confidence: 99%